Estudio del potencial eólico en Colombia y su complementariedad con fuentes de generación hidráulica (2021)
Colombia has a renewable installed capacity of close to 70% in hydroelectric generation. However, especially in dry periods, thermal generation (mostly based on natural gas) has played a dominant role in the country's generation. In this sense, thermal generation has considerably increased greenhouse gas (GHG) emissions, added to the fact that the proven reserves of natural gas are projected to a few years of supply, which makes its use unfeasible in the long term. Under this context, this work proposes to analyze the wind potential and complementarity with hydraulic generation in Colombia, from a climatological approach. The above, with the objective of determining if wind can be a viable alternative to guarantee the firmness of energy generation, reducing the dependence on non-renewable energies. For this purpose, wind atlases, data from hydrometeorological stations, reanalysis, satellite data, and climate change models are used. Based on this, the wind complementarity with basins for energy generation of the Sistema Interconectado Nacional (SIN) is established in regional terms and the places with the greatest wind potential in the country are determined. Subsequently, the offshore wind potential is studied in scenarios of climate variability and climate change. The results of this research indicate that there is a wide hydro-wind complementarity between different regions. It is worth highlighting the seasonal and interannual complementarity associated with ENSO of the most important hydroelectric region, with multiple regions of high wind potential such as the Caribbean Sea, among others. It was also determined, a higher net generation of wind farms in a location in the sea of La Alta Guajira in relation to equal installed capacities of important hydroelectric plants. This location also had a higher generation relative to the offshore potential of Buchan Deep in the North Sea. It was found that the migration phenology of migratory birds in the Caribbean coincides with the minimum offshore wind generation within the seasonal scale. Finally, multi-annual climate change projections predict that the offshore wind resource in the highest potential locations will remain stable or increase slightly. They also show for this century a likely seasonal compensation between reductions in precipitation in the Andes with increases in offshore wind potential in the Colombian Caribbean Sea and vice versa.